Reversible microfluidics device for precious metal electrodeposition and depletion yield studies. (20th August 2020) - Gouyon, Jérémie; d'Orlyé, Fanny; Simon, Craig; Griveau, Sophie; Sella, Catherine; Thouin, Laurent; Bedioui, Fethi; Varenne, Anne
Abstract: A new low-cost reversible Glass-NOA®-PDMS microfluidic device was designed for the study of recovery yield of precious metals present in acid media mimicking leach liquors for long-term recycling objectives. It offers the unique advantage of allowing easy washing of the microchannel and renewal of the electrode surface by simply repositioning the microband electrodes which allows this type of device to have a relatively much longer lifespan than irreversibly closed ones. It consists in a re-useable microchip with four graphite microbands electrodes, prepared by screen printing, to set-up an original amperometric device for both depletion and yield quantification. One upstream working electrode is devoted to the depletion of the metallic ions through their electrolysis by electrodeposition while the second downstream working microelectrode is used as real-time detection electrode to evaluate the depletion efficiency. The dimensions of the depletion electrode and of the channel were optimized thanks to numerical simulations for a given range of flow velocities. First, the performances of the device were assessed experimentally according to flow rate and applied potential under continuous flow, and then compared to theoretical predictions using an electrochemical probe, ferrocenemethanol. The proof of concept was then demonstrated for precious metal, by electroreduction of Pd(II) and Au(III) from acidic leach liquors under continuous flow, with a depletion yield of up to 89% and 71% respectively.